Controlled growth of Cu2−xS sheet-like nanoshells and Cu2−xS–CdS p–n junctions on Au nanorods with coupled plasmon resonances and enhanced photocatalytic activities. Issue 9 (30th January 2020) - Wang, Wei; Ma, Song; Chen, Kai; Wang, Peng-Fei; Liu, Qi-Yu; Zhou, Li; Wang, Qu-Quan
Abstract : Controlled growth of Cu2− x S sheet-like nanoshells and Cu2− x S–CdS p–n junctions on Au nanorods with enhanced photocatalytic activity. Abstract : In this study, we propose an approach to grow Cu2− x S sheet-like nanoshells on Au nanorods with the aid of Ag2 S auxiliary templates. The Ag2 S semi-shells are first grown on the side-surface of the Au nanorods and then, the Cu2− x S sheet-like nanoshells are selectively grown on the opposite side, which is beneficial for improving the controllability of the growth sites of the Cu2− x S sheet-like nanoshells. The Cu2− x S–CdS p–n junctions grown on Au nanorods are produced by replacing Ag + with Cd 2+ in the as-prepared Au/(Cu2− x S–Ag2 S), so that Au/(Cu2− x S–CdS) heterorods with non-central symmetric shells of Cu2− x S–CdS p–n junctions are formed. By carefully adjusting the effective thickness of the Cu2− x S–CdS junctions, the optimized photocatalytic activity of the Au/(Cu2− x S–CdS) heterorods is obtained, and it is about 1.62 and 1.22-fold that of Au/Cu2− x S and Au/CdS, respectively. The improved photocatalytic performance of the Au/(Cu2− x S–CdS) heterorods is attributed to the effective charge carriers at the interfaces of CdS–Au, Cu2− x S–Au and the Cu2− x S–CdS p–n junction. Our findings provide a strategy for the optimal design of plasmon–exciton heterostructures with improved photocatalytic activity.